Supporting Integration of Multiple Source Perspectives Through Dialogic Argumentation - Iordanou, Kalypso; Fotiou, Constantina (Frontline Learning Research, 2025)
We report a study examining, for the first time, the effectiveness of engagement in dialogic argumentation in relation to its ability to promote integration of multiple source perspectives in an argumentive writing task after reading controversial multiple texts. Sixty-four primary school students engaged in a dialog-based intervention aiming to support them to learn to argue. Participants’ argument skills have been improved and transferred to a writing task completed after reading novel multiple texts on new, non-intervention, topics. In particular, the experimental group participants showed gains in their ability to integrate multiple source perspectives in an argumentive writing task after reading controversial multiple texts, compared with a control group which engaged in business-as-usual school curriculum. Microgenetic data revealed a progressive development of experimental participants’ integration skill throughout their engagement in the argumentive discourse activity. The findings have important educational implications. They show that learning to argue by engaging in dialogic argumentation is a promising pathway for supporting the ability to integrate multiple source perspectives after reading controversial multiple texts.